2022
DOI: 10.3390/polym14214585
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Neodymium (Nd) from Aqueous Solutions Using Spirulina platensis sp. Strains

Abstract: Rare earth elements such as neodymium (Nd) are important elements used mainly in developing new technologies. Although they are found in low concentrations in nature, they can be obtained by extracting solid samples such as phosphogypsum. Among the techniques, adsorption has been used successfully with several adsorbent materials. In this work, two strains of Spirulina platensis (LEB-18 and LEB-52) were employed as biosorbents for efficiently removing the Nd element from the aqueous media. Biosorption tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…At the solid-liquid interface, the system's pH has a crucial role in the adsorption process. pH pzc is the point, whereas the adsorbent's surface charge is null [16,17]. Zeta potential values of Ni-Al-LDH decreased as the pH increased (see Fig.…”
Section: Point Of Zero Charge (Ph Pzc ) and Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…At the solid-liquid interface, the system's pH has a crucial role in the adsorption process. pH pzc is the point, whereas the adsorbent's surface charge is null [16,17]. Zeta potential values of Ni-Al-LDH decreased as the pH increased (see Fig.…”
Section: Point Of Zero Charge (Ph Pzc ) and Effect Of Phmentioning
confidence: 99%
“…Among several techniques to concentrate REEs, adsorption is the most common due to its easy operation and lowcost involvement [13,14]. REEs can be adsorbed on many different materials, such as silica [13], clays, minerals, zeolites [15], chitosan materials [16], biomass waste [17], and covalent organic frameworks [18]. In addition, layered double hydroxides (LDH) are also very effective materials for adsorbing ions and compounds, including REEs [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Two strains of Spirulina platensis were applied to recover Nd from batch solutions. Both strains showed high adsorption capacity: 72.5 mg/g for the LEB-18 strain and 48.2 mg/g for LEB-52 [ 21 ]. Approximately 80% of Yb ions were adsorbed by spirulina from simulated mine wastewater [ 22 ], and 87.62% of the ions were absorbed from an aqueous solution [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to their findings, Nd(III) has a maximum adsorption capacity of 69.24 mg/g. Lima et al 19 employed two strains of Spirulina platensis (LEB-18 and LEB-52) for the recovery of Nd(III) from aqueous solutions. They reported that LEB-18 possesses a maximum biosorption capacity of 72.5 mg/g and LEB-52 has a maximum biosorption capacity of 48.2 mg/g.…”
Section: Introductionmentioning
confidence: 99%